Hubungan Tingkat Pengetahuan Dengan Kepatuhan Ibu Hamil Dalam Melakukan Imunisasi Tetanus Toksoid Di Puskesmas Dumbo Raya Kota Gorontalo: The Relationship Between Knowledge Level and Compliance of Pregnant Women in Receiving Tetanus Toksoid Immunization at Dumbo Raya Public Health Center Gorontalo City - Paputungan, Rofika; Hafid, Ridha; Hiola, Dewi Suryaningsi (Jurnal Keperawatan Sumba (JKS), 2025)
Based on the World Health Organization data, it is estimated that the global incidence of tetanus is approximately 0.5-1 million cases, with neonatal tetanus accounting for 50% 0f tetanus-related deaths in developing countries, including Indonesia (Mariyana & Sihombing, 2021). Tetanus toxoid immunization is one of the preventive measures to control the risk factors for maternal and neonatal mortality. This study aims to determine the relationship between the knowledge level and the compliance of pregnant women in receiving tetanus toxoid immunization at Dumbo Raya Public Health Center, Gorontalo City. This study employed a quantitative method with an observational approach. The sample consisted of 40 pregnant women in their first and second trimesters, selected using non-probability sampling. Data collection included questionnaire and checklist. Data analysis was peformed using univariate and bivariate analysis. The findings show that most pregnant women have good knowledge and comply with tetanus toxoid immunization. Chi-square analysis reveals a p-value = 0.002< α = 0.05, indicating a significant relationship between the knowledge level of pregnant women and their compliance with tetanus immunization. This study is expected to serve as input for public health centers to enhance their health promotion efforts related to tetanus immunization among pregnant women. This research has passed the Health Assessment Ethics Commission of Gorontalo State University with Number: 070A/UN47.B7/KE/2024 starting June 20, 2024.